Biochemical variability in sponges across the Caribbean basin. Issue 3 (1st July 2021) - Clayshulte Abraham, Amelia; Gochfeld, Deborah J.; Macartney, Keir; Mellor, Amelia; Lesser, Michael P.; Slattery, Marc
Abstract: Sponges are a diverse phylum of sessile filter‐feeding invertebrates that are abundant on Caribbean reefs and provide essential ecological services, including nutrient cycling, reef stabilization, habitat, and food for a variety of fishes and invertebrates. As prominent members of the benthic community, and thus potential food resources, factors determining the biochemical and energetic content of sponges will affect their trophic contributions to coral reef ecosystems. In order to evaluate the influence of geographic variation on biochemical composition and energetic content in the tissue of sponges, we collected several common and widespread species ( Agelas conifera, Agelas tubulata, Amphimedon compressa, Aplysina cauliformis, Niphates amorpha, Niphates erecta, and Xestospongia muta ) from multiple shallow reefs in four countries across the Caribbean Basin, including Belize, Curaçao, Grand Cayman, and St. Croix, U.S. Virgin Islands. In addition, we correlated inherent species‐level traits, including the production of antipredator chemical defenses and the relative abundance of microbial symbionts, with biochemical and energetic content. We found that energetic content was higher in sponges with antipredator chemical defenses, and was significantly correlated with the concentration of chemical extracts from these sponges. We also noted that sponges with high microbial abundance contained significantly more soluble protein than sponges with low microbial abundance. Finally, both biochemical and energetic content varied significantly among sponges from different locations; sponges from Grand Cayman had the highest lipid and energetic content, whereas sponges from Belize had the highest carbohydrate content but lowest energetic content. Despite similar environmental conditions at these sites, our results demonstrate that biochemical and energetic content of sponges exhibits geographic variability, with potential implications for the trophic ecology of sponges throughout the Caribbean Basin.